2021
DOI: 10.3389/fimmu.2021.672752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epstein-Barr Virus DNA on the Incidence and Severity of Arthritis in a Rheumatoid Arthritis Mouse Model

Abstract: ObjectiveWe recently demonstrated that EBV DNA is correlated with proinflammatory responses in mice and in rheumatoid arthritis (RA) patients; hence, we utilized an RA mouse model to examine whether EBV DNA enhances the risk and severity of arthritis and to assess its immunomodulatory effects.MethodsC57BL/6J mice were treated with collagen (arthritis-inducing agent), EBV DNA 6 days before collagen, EBV DNA 15 days after collagen, Staphylococcus epidermidis DNA 6 days before collagen, EBV DNA alone, or water. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…They were co-housed in nonindividually ventilated cages (non-IVC) in the same room and had access to unlimited water and food. Induction of arthritis was carried out as previously described in a recent study ( 15 ). The study included an arthritis control group that received the inducing agent and the booster.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were co-housed in nonindividually ventilated cages (non-IVC) in the same room and had access to unlimited water and food. Induction of arthritis was carried out as previously described in a recent study ( 15 ). The study included an arthritis control group that received the inducing agent and the booster.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research by our group showed that EBV DNA induces proinflammatory responses in mice and that the EBV DNA load in patients with RA corresponds to a higher serum level of IL-17A, a proinflammatory cytokine ( 13 , 14 ). In addition, a recent study by our group showed that EBV DNA enhances the incidence and severity of RA in a collagen-induced arthritis (CIA) mouse model ( 15 ). Hence, in this study, we intended to determine the effect of EBV DNA on the composition and diversity of intestinal microbiota and identify whether this plays a role in arthritis development in this mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Using endosomal Toll-like receptor inhibitors, we reported that this immune signaling pathway was involved in the increase in IL-17A levels [ 5 ]. Therefore, EBV induces a pro-autoimmune response causing an elevation in systemic and tissue IL-17A levels, thus acting as a risk factor for the development of autoimmune diseases [ 6 ]. Recent studies have suggested that EBV may contribute to the pathophysiology of inflammatory bowel disease (IBD), a chronic inflammatory condition with a rising incidence worldwide [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of RA has not yet been fully elucidated and may be related to a variety of genetic and environmental factors, of which the strongest risk factors include female gender, family history of RA, genetic factors, and exposure to tobacco smoke (3). In addition, infections are also considered to be an important cause of RA, and some bacterial and viral infections including periodontal bacteria, Epstein-Barr virus, parvovirus B19 and Chikungunya virus are considered to be associated with RA (4)(5)(6)(7). The mechanism of how infection affects RA remains undetermined, and it is commonly believed that the antigen of the pathogen may trigger cross-reactivity between autoantigen and viral proteins through a molecular mimicry mechanism (7).…”
Section: Introductionmentioning
confidence: 99%